Design and Development of Ceramic Information System Based on Object Oriented Programming - Mari Rahmawati; Amin Kusniawati; Rangga Kori Lesmana (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2020)
The author designed an object oriented programming based sales application using use case diagrams, activity diagrams, sequence diagrams, deployment diagrams, entity relationship diagrams, logical record structures, and user interfaces. The design of this information system is expected to produce sales application programs ranging from customer data input, input data of goods, input of sales orders, print out of travel documents, print invoices, cash receipts input, print payment receipts to print reports so that sales applications can have a positive impact on the course of business which is built, reducing duplicated functions, and errors caused by human errors. With the design of a sales application, the problems that exist in the manual system can be resolved such as the system will not receive incomplete data, the system can make automatic numbering, and minimize errors that occur due to humans (human error), reduce the amount of paper usage, report generation can done easily and quickly because the data is processed by the system.Keywords: Design, Sales, Object Oriented Programming.